14C‐Free Carbon Is a Major Contributor to Cellular Biomass in Geochemically Distinct Groundwater of Shallow Sedimentary Bedrock Aquifers. Issue 3 (15th March 2019) - Schwab, Valérie F.; Nowak, Martin E.; Elder, Clayton D.; Trumbore, Susan E.; Xu, Xiaomei; Gleixner, Gerd; Lehmann, Robert; Pohnert, Georg; Muhr, Jan; Küsel, Kirsten; Totsche, Kai U.
Abstract: Despite the global significance of the subsurface biosphere, the degree to which it depends on surface organic carbon (OC) is still poorly understood. Here, we compare stable and radiogenic carbon isotope compositions of microbial phospholipid fatty acids (PLFAs) with those of in situ potential microbial C sources to assess the major C sources for subsurface microorganisms in biogeochemical distinct shallow aquifers (Critical Zone Exploratory, Thuringia Germany). Despite the presence of younger OC, the microbes assimilated 14 C‐free OC to varying degrees; 31% in groundwater within the oxic zone, 47% in an iron reduction zone, and 70% in a sulfate reduction/anammox zone. The persistence of trace amounts of mature and partially biodegraded hydrocarbons suggested that autochthonous petroleum‐derived hydrocarbons were a potential 14 C‐free C source for heterotrophs in the oxic zone. In this zone, Δ 14 C values of dissolved inorganic carbon (−366 ± 18‰) and 11MeC16:0 (−283 ± 32‰), an important component in autotrophic nitrite oxidizers, were similar enough to indicate that autotrophy is an important additional C fixation pathway. In anoxic zones, methane as an important C source was unlikely since the 13 C‐fractionations between the PLFAs and CH4 were inconsistent with kinetic isotope effects associated with methanotrophy. In the sulfate reduction/anammox zone, the strong 14 C‐depletion of 10MeC16:0 (−942 ± 22‰), a PLFA common in sulfate reducers, indicated that those bacteria were likely to play a critical part in 14 C‐free sedimentary OC cycling. Results indicated that the 14 C‐content of microbial biomass in shallow sedimentary aquifers results from complex interactions between abundance and bioavailability of naturally occurring OC, hydrogeology, and specific microbial metabolisms. Key Points: Microbial lipids (PLFAs) and C sources in aquifers with different subsurface‐surface relationships were analyzed for their 14 C‐content Subsurface microbes incorporated 14 C‐free C in proportions depending on the physiological strategies of the microorganism community Autotrophic nitrite oxidation occurred in oxic zone, whereas heterotrophy on sedimentary C dominated in sulfate reduction/anammox zone